A generic post-deblocking filter for block based image compression algorithms - Francisco, Nelson C.; Rodrigues, Nuno M.M.; da Silva, Eduardo A.B.; de Faria, Sérgio M.M. (Signal processing. Image communication, 2012)
In this paper we propose a new post-processing deblocking technique that is independent of the compression method used to encode the image. The development of this filter was motivated by the use of Multidimensional Multiscale Parser (MMP) algorithm, a generic lossy and lossless compression method. Since it employs an adaptive block size, it presents some impairments when using the deblocking techniques presented in the literature. This led us to the development of a new and more generic deblocking method, based on total variation and adaptive bilateral filtering. The proposed method was evaluated not only for still images, but also for video sequences, encoded using pattern matching and transform based compression methods. For all cases, both the objective and subjective quality of the reconstructed images were improved, showing the versatility of the proposed technique. ► We propose a post-processing image deblocking method, independent of the compression algorithm. ► The proposed method is based on total variation analysis and adaptive bilateral filtering. ► This method was evaluated for images encoded using MMP, JPEG, H.264/AVC and HEVC. ► For all codecs, results competitive with state-of-the-art deblocking methods were achieved. ► For all cases, both the objective and subjective quality of the reconstructed image were improved.